The Position of a Stepfather Towards a Stepchild: Analysis of Population Administrative Law and Islamic Law - Muhammad Fikri Akbari (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
Every child has the fundamental right to obtain a legal identity through legal identity documents, especially birth certificates. However, problems arise when in practice stepfathers are often positioned as father figures who are then included in birth certificates. From a normative perspective, state administrative law explicitly recognizes only biological fathers as legal parents who can be recorded. Meanwhile, Islamic law also rejects the position of stepfathers as marriage guardians and heirs, because there is no nasab bond or blood relationship between stepfathers and stepchildren. This research uses a normative-empirical approach through the study of legislation, the Compilation of Islamic Law, and the reality of social practices in society. The results show that there is a misalignment between legal norms and social reality, causing problems in the form of unorganized population administration, unclear legal status of children, and the risk of marriage invalidity. Therefore, efforts are needed to strengthen socialization regarding the position of stepfathers from a legal perspective, so that legal certainty is maintained while paying attention to the social needs of the community.